Heterogeneous fluid flow in fractured layered carbonates and its implication for generation of incipient karst. (September 2017) - Wang, X.; Lei, Q.; Lonergan, L.; Jourde, H.; Gosselin, O.; Cosgrove, J.
Highlights: The bedding plane-to-joints aperture ratio dominates the degree of flow heterogeneity along the bedding planes in karstified rock. Three distinct flow regimes are identified in these systems that correspond to different aperture ratios. A method for predicting the type and preferential location of incipient karst is proposed. Abstract: We use numerical models to investigate fluid flow in layered fractured carbonate rocks, and specifically to investigate the effects of the structural and hydraulic properties of both joints and bedding planes on flow localization. Synthetic fracture networks made up of two jointed layers separated by a horizontal bedding plane are generated to represent the typical layered fracture systems often formed in carbonate rocks. A uniform aperture field is assumed for each joint set and for the bedding plane, but different joint sets and the bedding plane can have non-identical values. The aperture ratio of the joint sets to the bedding plane is found to dominate the behaviour of flow heterogeneity on the bedding plane. Three distinct flow regimes, i.e. joint-dominated, transitional and bedding plane-dominated, are recognized. The magnitude of the aperture ratio controls which flow regime develops. We further suggest that the different flow regimes may be responsible for the initiation of different types of incipient karst morphologies observed in nature: pipe karst, stripe karst and sheet karst.